The perfume thief - Schaffert, Timothy (Doubleday, a division of Penguin Random House LLC, 2021)
"Clementine, sometimes known as Judge, is a 72-year-old reformed con artist with a penchant for impeccably tailored suits. Her life of crime has led her from the uber-wealthy perfume junkies of belle epoque Manhattan, to the scented butterflies of Costa Rica, to the spice markets of Marrakesh, and finally the bordellos of Paris, where she settles down and opens a legitimate shop bottling her favorite extracts for the ladies of the cabarets. In 1941 as the Germans stranglehold on the city tightens, Clem's perfume-making attracts the notice of Oskar Voss, a francophile Nazi bureaucrat, who comes to demand Clem's expertise and loyalty in his mysterious play for Hitler's favor. Clem has no choice but to surrender fully to the con, but even though she knew playing the part of collaborator would be dangerous, she never imagined it would be so painfully intimate. At Oskar's behest and in an effort to win his trust, Clem tells him the full story of her life and loves, this time without the cover of the lies she came to Paris to escape. Complete with romance, espionage, champagne towers and haute couture, this full-tilt sensory experience is a dazzling portrait of the underground resistance of twentieth century Paris and a passionate love letter to the power of beauty and community in the face of insidious hate"--